2015
DOI: 10.1177/1362361315585916
|View full text |Cite
|
Sign up to set email alerts
|

Self and informant reports of mental health difficulties among adults with autism findings from a long-term follow-up study

Abstract: Data on psychiatric problems in adults with autism are inconsistent, with estimated rates ranging from around 25% to over 75%. We assessed difficulties related to mental health in 58 adults with autism (10 females, 48 males; mean age 44 years) whom we have followed over four decades. All were of average non-verbal intelligence quotient when diagnosed as children. Overall ratings of mental health problems were based on data from the Family History Schedule (Bolton et al., 1994). Informant reports indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 52 publications
(86 reference statements)
7
68
0
Order By: Relevance
“…Presence of psychiatric comorbidities were common in this group of individuals with ASD (58%) and comparable to other studies (41% in overall sample; 65% in those with mild learning difficulties; Morgan et al 2003). Depression/anxiety were present in approximately one third of this group of individuals with ASD; a similar proportion to that found in a recent study where adults with ASD reported their own experiences of depression and anxiety (Moss et al 2015). In a larger sample including adults with learning disability rates of depression were similar and even higher in those with mild learning disability (46%; Morgan et al 2003).…”
Section: Discussionsupporting
confidence: 88%
“…Presence of psychiatric comorbidities were common in this group of individuals with ASD (58%) and comparable to other studies (41% in overall sample; 65% in those with mild learning difficulties; Morgan et al 2003). Depression/anxiety were present in approximately one third of this group of individuals with ASD; a similar proportion to that found in a recent study where adults with ASD reported their own experiences of depression and anxiety (Moss et al 2015). In a larger sample including adults with learning disability rates of depression were similar and even higher in those with mild learning disability (46%; Morgan et al 2003).…”
Section: Discussionsupporting
confidence: 88%
“…The first condition is anorexia nervosa (AN), which, along with other eating disorders, is diagnosed at a significantly higher rate in females than in males [74]. Individuals with AN are also significantly more likely to have ASD symptoms than the general population [75].…”
Section: Anorexia Nervosamentioning
confidence: 99%
“…Anxiety problems are also more commonly found in females with and without ASD [82,83], although are still highly prevalent amongst males [84]. It has been suggested that anxiety disorders may 'mask' some ASD symptoms in women, as the anxiety may be the most pressing clinical concern and so underlying ASD difficulties remain unidentified [68,85]. Indeed, autistic women who were diagnosed in adulthood report high levels of anxiety and diagnoses of anxiety disorders from adolescence, and often first present clinically in mental health services, seeking help for their anxiety problems [61].…”
Section: Anxietymentioning
confidence: 99%
“…Similarly, having a diagnosis of ASD may in some cases further exacerbate other problems, making it harder to cope. This is particularly important to examine in more detail in light of the vast literature exploring the common co-morbidities which frequently present in individuals with ASD, most notably, mood disorders such as depression and anxiety (e.g., Ghaziuddin, Ghaziuddin, & Greden, 2002;Hammond & Hoffman, 2014;Matson & Williams, 2014;Moss, Howlin, Savage, Bolton, & Rutter, 2015;Bruggink, Huisman, Vuijk, Kraaij, & Garnefski, 2016), and behavioral disorders such as attention-deficit/hyperactivity disorder (ADHD) (e.g., Chen et al, 2015;Taylor, Charman, & Ronald, 2015;Antshel, Zhang-James, Wagner, Ledesma, & Faraone, 2016). Such comorbidities may further intensify an individual with ASD's impaired ability to cope with problems in his or her life.…”
Section: Discussionmentioning
confidence: 99%